Debt relief for poor countries - Addison, Tony (Palgrave Macmillan, 2004)
After a massive international campaign calling attention to the development impact of foreign debt, the Heavily Indebted Poor Countries (HIPC) initiative is now underway. But will the HIPC Initiative meet its high expectations? Will debt relief substantially raise growth? How do we make sure that debt relief benefits poor people? And how can we ensure that poor countries do not become highly indebted again? These are some of the key policy issues covered in this rigorous and independent analysis of debt, development, and poverty.